2015
DOI: 10.1371/journal.pone.0129676
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-AKT Signaling via Nrf2 Protects against Hyperoxia-Induced Acute Lung Injury, but Promotes Inflammation Post-Injury Independent of Nrf2 in Mice

Abstract: Lung epithelial and endothelial cell death accompanied by inflammation contributes to hyperoxia-induced acute lung injury (ALI). Impaired resolution of ALI can promote and/or perpetuate lung pathogenesis, including fibrosis. Previously, we have shown that the transcription factor Nrf2 induces cytoprotective gene expression and confers protection against hyperoxic lung injury, and that Nrf2-mediated signaling is also crucial for the restoration of lung homeostasis post-injury. Although we have reported that PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 43 publications
8
51
0
Order By: Relevance
“…These results suggested that melatonin exhibited antioxidant effects by activating Nrf2 signaling pathway. Previous research has demonstrated that the PI3K/AKT pathway plays a critical role in modulating Nrf2/HO-1 protein expression as an upstream signaling molecule [22]. In this study, we found melatonin upregulated the phosphorylation of PI3K and AKT.…”
Section: Discussionsupporting
confidence: 60%
“…These results suggested that melatonin exhibited antioxidant effects by activating Nrf2 signaling pathway. Previous research has demonstrated that the PI3K/AKT pathway plays a critical role in modulating Nrf2/HO-1 protein expression as an upstream signaling molecule [22]. In this study, we found melatonin upregulated the phosphorylation of PI3K and AKT.…”
Section: Discussionsupporting
confidence: 60%
“…It is important to identify the upstream regulatory molecules associated with IQGAP1. According to some studies, the PI3K/Akt pathway is not only a crucial regulatory molecule for various cellular functions, but also important in transduction signalling underlying endothelial barrier function during sepsis . In the present study, we found that SV/SV‐NPs activated the PI3K/Akt pathway and promoted Akt phosphorylation, which was inhibited by LPS.…”
Section: Discussionsupporting
confidence: 65%
“…According to some studies, the PI3K/Akt pathway is not only a crucial regulatory molecule for various cellular functions, but also important in transduction signalling underlying endothelial barrier function during sepsis. [50][51][52][53] In the present study, we found that SV/SV-NPs activated the PI3K/Akt pathway and promoted Akt phosphorylation, which was inhibited by LPS. We then used the PI3K inhibitor LY294002 to determine whether the PI3K/Akt pathway had a mediating function in SV/SV-NPs-induced barrier protection.…”
Section: Discussionsupporting
confidence: 58%
“…It plays a cytoprotective role in detoxification and chemoprevention through the activation of phase II gene expression [15,16]. Previous studies reported that Nrf2 and its target genes (heme oxygenase 1, NADPH quinone oxidoreductase, and biliverdin reductase), decreased hyperoxia‐induced acute lung injury and were associated with alveolar macrophage oxidative stress in smoking patients with PSP [7,17].…”
Section: Introductionmentioning
confidence: 99%